2013
DOI: 10.1534/genetics.112.147645
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Targeted Mutagenesis in Medaka Using Custom-Designed Transcription Activator-Like Effector Nucleases

Abstract: Transcription activator-like effector nucleases (TALENs) have become powerful tools for targeted genome editing. Here we demonstrate efficient targeted mutagenesis in medaka (Oryzias latipes), which serves as an excellent vertebrate model for genetics and genomics. We designed and constructed a pair of TALENs targeting the medaka DJ-1 gene, a homolog of human DJ-1 (PARK7). These TALENs induced a number of insertions and deletions in the injected embryos with extremely high efficiency. This induction of mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 41 publications
0
84
0
Order By: Relevance
“…TALEN technology has been used to knock out endogenous genes in medaka and detect gene disruption. Unfortunately, in earlier reports, there was no loss of gene function and the expected phenotype was not detected after gene knockout (Ansai et al 2013(Ansai et al , 2014. In this present study, to show that TALENs can be used to conduct gene knockout and gene-editing studies in medaka, a pre-built modified TALEN (Liu et al 2014) system was used to knock out an exogenous transgene in medaka.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…TALEN technology has been used to knock out endogenous genes in medaka and detect gene disruption. Unfortunately, in earlier reports, there was no loss of gene function and the expected phenotype was not detected after gene knockout (Ansai et al 2013(Ansai et al , 2014. In this present study, to show that TALENs can be used to conduct gene knockout and gene-editing studies in medaka, a pre-built modified TALEN (Liu et al 2014) system was used to knock out an exogenous transgene in medaka.…”
Section: Introductionmentioning
confidence: 78%
“…However, unfortunately, the expected phenotype was not detected after gene knockout (Ansai et al 2013). This demonstrated the potential application of TALEN technology in medaka, but it also showed that TALENs could generate DSB at target gene-specific sites that may or may not affect the translation of target or off-target genes.…”
Section: Discussionmentioning
confidence: 99%
“…In medaka (Oryzias latipes), TALEN mRNA concentrations from 10 ng/ml to 300 ng/ml per TALEN arm were used. 55 In murine embryos, TALEN mRNAs with concentrations of 20 and 50 ng/ml successfully generated mutations. 56 The possibility of off-target effects caused by higher concentrations of TALEN mRNAs has raised some concern in the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…AD transcriptional activation domain, tet tetracycline resistance, spec spectinomycin resistance, amp ampicillin resistance, HIS3 histidine biosynthesis marker gene, NLS nuclear localization signal, B BamHI, S SphI pairs to mediate the formation of small insertions and deletions in a gene of interest, thereby altering or inactivating the gene product. More complex chromosomal modifi cations can be generated when two TALENs pairs are used to create DSBs simultaneously, leading to the formation of large deletions and inversions (Ansai et al 2013 ;Carlson et al 2012 ;Ma et al 2012 ). One landmark study demonstrated that TALENs could effi ciently modify human genes, namely NTF3 and CCR5 (Miller et al 2011 ).…”
Section: Modifying Genes Using Tal Effector Fusion Proteinsmentioning
confidence: 99%